The Role of Education in Cultivating Patriotism Among Children at ICC Muar - Baswara, Daffa; Rumandhani, Aditiya Eka; Julfian, Julfian; Adika, Muhammad; Handayani, Trisakti; Fitria, Munaya (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
This article delves into the role of education in instilling a love for the homeland in children. As a nation blessed with diverse cultures and natural biodiversity, Indonesia requires an education system capable of nurturing a generation that cherishes their homeland. Education plays a pivotal role in nurturing this sense of patriotism in children. Through education, children can learn about the history and culture of Indonesia, as well as comprehend the natural diversity within the country. By immersing themselves in these aspects, children can grasp the importance of preserving Indonesias environment and cultural heritage. Furthermore, education helps children understand nationalistic values such as unity and the spirit of mutual cooperation, fostering a deep love and pride for Indonesia. Education also empowers children to actively participate in activities aimed at advancing Indonesia, including environmental initiatives, social projects, and humanitarian efforts. Through such participation, children can directly experience the benefits of endeavors made to progress Indonesia. In conclusion, education plays a fundamental role in nurturing patriotism in children. Through education, children learn about Indonesias history, culture, and natural diversity, understand nationalistic values, and develop the ability to contribute to activities that advance Indonesia. Consequently, education has the power to shape a generation that loves and takes immense pride in Indonesia.